Efficient 10 ns-scale 2-μm optical parametric oscillator based on 1064 nm pump source - Chen, Si-Ying; Yang, Yun-Fei; Li, Yun-Fei; Wang, Gong; Yu, Yu; Du, Hai-Yang; Cao, Feng-Li; Yin, Hong-Wei; Zhu, Chen-Yu; Wang, Yu-Lei; Lu, Zhi-Wei (Frontiers in Physics, 2024)
Lasers operating around 2-µm have been extensively researched for various applications, such as LiDAR, remote sensing, optical communication, and medicine. One of the approaches to generate 2µm emission is to employ an optical parametric oscillator pumped by 1-µm laser; however, improving the 2-µm laser conversion efficiency of optical parametric oscillators is still a challenge. Based on the high nonlinear coefficient of the KTP crystal at 2-µm, an optical parametric oscillator with high efficiency was realized using a laser diode (LD) side-pumped electro-optic Q-modulated Nd: YAG laser. The cavity was designed and optimized based on mode matching to increase the peak power density of the pump laser. Different powers were obtained for different pump laser focusing conditions, and the maximum power was obtained when the KTP crystal was placed in front of the pump laser focus. The output characteristics of the KTP at different phase-matching angles were also investigated. An output power of 2.44 W and an output pulse width of 9.04 ns were obtained at 2154.4 nm with an optical-to-optical conversion efficiency of 23.39% and a slope efficiency of 36.09%.